Ghrelin: Ghrelin as a Regulatory Peptide in Growth Hormone Secretion - Khatib, Nazli (JCDR Research and Publications (P) Limited, 2014)
Background: Ghrelin is a type of growth hormone (GH) secretagogue that stimulates the release of GH. It is a first hormone linking gastrointestinal-pituitary axis. Objective: This review highlights the interaction of ghrelin with GHRH and somatostatin to regulate the secretion of GH and intends to explore the possible physiological role of the ghrelin-pituitary-GH axis linkage system. Observation: Ghrelin is highly conserved among species and is classified into octanoylated (C8:0), decanoylated (C10:0), decenoylated (C10:1) and nonacylated,ghrelin. Acylated ghrelin is the major active form of human ghrelin. The primary production site of ghrelin is the stomach, and it interacts with stomach ghrelin as well as hypothalamic GHRH and somatostatin in the regulation of pituitary GH secretion. Ghrelin stimulate GH release through the GHS receptor to increase intracellular Ca2+ ([Ca2+] levels via IP3 signal transduction pathway. Ghrelin is a specific endogenous ligand for the GHS receptor and provides a definitive proof of the occurance of a GHS–GHS receptor signalling system in the regulation of GH secretion. Conclusion: Studies suggests that ghrelin is a powerful pharmacological agent that exerts a potent, time-dependent stimulation of pulsatile secretion of GH.